Ichnology : Organism-Substrate Interactions in Space and Time - Buatois, Luis A.; Mángano , M. Gabriela (Cambridge : Cambridge, 2011)
Ichnology is the study of traces created in the substrate by living organisms. This is the first book to systematically cover basic concepts and applications in both paleobiology and sedimentology, bridging the gap between the two main facets of the field. It emphasizes the importance of understanding ecologic controls on benthic fauna distribution and the role of burrowing organisms in changing their environments. A detailed analysis of the ichnology of a range of depositional environments is presented using examples from the Precambrian to the recent, and the use of trace fossils in facies analysis and sequence stratigraphy is discussed. The potential for biogenic structures to provide valuable information and solve problems in a wide range of fields is also highlighted. An invaluable resource for researchers and graduate students in paleontology, sedimentology and sequence stratigraphy, this book will also be of interest to industry professionals working in petroleum geoscience.
Includes References 297-346p.; Index 347-358p.
Keywords: Paleoecology; Ichnology